2014 IEEE 12th International New Circuits and Systems Conference (NEWCAS) 2014
DOI: 10.1109/newcas.2014.6933987
|View full text |Cite
|
Sign up to set email alerts
|

Architectural impacts of emerging transistors

Abstract: At present there is much effort to determine if emerging information processing devices could have a positive impact on the performance of non-Boolean/non-von Neumann computer architectures. We explore this topic here by specifically considering how emerging transistor technologies might impact cellular neural networks (CNNs). For CNNs, prior work suggests that new transistor structures could be employed to better facilitate non-binary outputs -that in turn reduce the number of template/programming operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, non-linear templates often reduce the number of programming steps required to solve a particular problem, when compared to an algorithm that employs only linear templates. Initial work [44] suggests that non-linearities associated with SymFETs can be used to efficiently realize non-linear templates. As an example, to perform thresholding on an interval using a band pass filter, three sequential linear operations are needed.…”
Section: Role Of Emerging Technologies In Vision Systemsmentioning
confidence: 99%
“…However, non-linear templates often reduce the number of programming steps required to solve a particular problem, when compared to an algorithm that employs only linear templates. Initial work [44] suggests that non-linearities associated with SymFETs can be used to efficiently realize non-linear templates. As an example, to perform thresholding on an interval using a band pass filter, three sequential linear operations are needed.…”
Section: Role Of Emerging Technologies In Vision Systemsmentioning
confidence: 99%
“…Previous research [9,10,11,12] have shown positive results by utilizing emerging devices in multiple CNN contexts. Specifically, [9] shows TFETs can be utilized as nonlinear resistive element in CNNs to improve power efficiency without sacrificing performance.…”
Section: Introductionmentioning
confidence: 99%